Comparison of river quality indices to detect the impact of organic pollution and water abstraction in Hindu Kush-Himalayan rivers of Nepal - Feld, Christian Karl; Tangelder, Marijn; Klomp, Maaike Johanna; Sharma, Subodh (Journal of Wetlands Ecology, 2011)
Several assessment methods exist for river quality classification in the Hindu Kush-Himalayan region. While rapid field bioassessment (RFB)1 applies on-site screening protocols, more sophisticated multi-habitat sampling (MHS) is employed to generate biotic scores using benthic macroinvertebates as bioindicators. This study presents the comparison of River Quality Classifications (RQC) according to i) 40 RFB records based on two slightly different RFB protocols and ii) 20 qualitative benthic macroinvertebrate samples used to calculate two different scores (average scores per taxon; ASPT). Sensory attributes, such as odour, colour, foam and epilithic algal cover, were used in addition to biological samples for RFB. All samples were taken at two river basins in Nepal, the Punyamata river (12 stations, stressor: organic pollution) and the Khimti river (8 stations, stressor: damming and water abstraction). RQCs revealed organic pollution to impact benthic invertebrate communities in the Punyamata river, while the impact of water abstraction and damming was not detectable in the Khimti basin based on the methods compared. Furthermore, a pollution gradient was clearly detectable based on 66 macroinvertebrate families and genera found in our samples. Our results confirm the applicability of RFB protocols and scoring systems to asses the impact of organic pollution in Nepalese rivers. Further research, however, will be required to adjust the protocols and taxon scores to assess also the impact of other stressors present in the region. Key words: Rapid field bioassessment; benthic macroinvertebrates; NEPBIOS; ASPT; water quality; Punyamata; Khimti DOI: 10.3126/jowe.v4i0.2545 Journal of Wetlands Ecology, (2010) Vol. 4, pp 112-127